“Estudio de Factibilidad para la Creación de un restaurante oculto en la ciudad de Latacunga”. - Ayala Aguirre, Alex Fernando (2021)
The exponential growth of the offer in the food and beverage industry constitutes a challenge for those who decide to undertake in the gastronomy business. For this reason, the number of ventures with disruptive business models is increasing, which seek to generate added value and penetrate the entry barriers to highly competitive markets; And this is the specific case of the "Hidden Restaurants" or "Ghost Restaurant", which propose the idea of not having a physical place for customer service, but rather focus on offering high quality products, rapid preparation and home delivery, thus reducing operating and investment costs. For which, the theoretical foundations that support the viability of the proposal were analyzed, in addition, through the market study, a target market could be identified, which represents a growing market that adjusts its trends and preferences to the proposed proposal. On the other hand, the proposal was delimited in order to better understand the line of business, the environment in which it will be developed and, finally, the economic viability, through a financial analysis which determined the feasibility of the proposal, yielding a current value. net of $27559.80, an IRR of 29.07% and a recovery period for the investment of 3 years and 10 months.